Impact of different roasting conditions on sensory properties and health-related compounds of oat products. (1st March 2020) - Schlörmann, W.; Zetzmann, S.; Wiege, B.; Haase, N.U.; Greiling, A.; Lorkowski, S.; Dawczynski, C.; Glei, M.
Highlights: Oat kernels, thin and thick flakes were roasted under different conditions. Sensory properties, health-related compounds and viscosities of raw and roasted products were analysed. Sensory quality was improved, acrylamide levels increased and viscosity decreased. Protein, fat, starch, β-glucan, dietary fibre were not or only marginally affected. Moderate roasting preserves valuable compounds and improves sensory properties. Abstract: Due to their high content of β-glucan, the consumption of oat products can contribute to a healthy diet. Roasting may improve sensory properties but could also affect the nutritional value of oat products. Therefore, the aim of the present study was to analyse the impact of different roasting conditions (140–180 °C, approx. 20 min) on sensory quality, health-related compounds (e.g. acrylamide, β-glucan) and viscosities of oat kernels and flakes. Roasting resulted in oat flakes with improved sensory properties. Acrylamide formation increased with higher roasting temperatures in kernels, thin and thick flakes. Contents of fat, protein, starch and β-glucan were not affected by roasting, whereas dietary fibre fractions were marginally modulated. Viscosities were significantly reduced with increasing roasting temperatures. The results indicate that roasting up to 160 °C is a processing technique with potential to generate oat products with improved sensory quality and favourable nutritional composition.